Comparative MHD analysis of IPD plasma accelerator work with different electrode polarization - Rabiński, M.; Zdunek, K. (Вопросы атомной науки и техники, 2008)
During the Impulse Plasma Deposition (IPD) process of surface engineering plasma is generated in the working gas due to a high-voltage high-current discharge, ignited within an interelectrode region of a coaxial accelerator. A continually growing demand for deeper understanding of the process was the reason to investigate the plasma flow phenomena numerically. The paper reports computational studies of the IPD accelerator with internal cathode. The detailed structure of the discharge region was described by a two-dimensional, two-fluid magnetohydrodynamic approach. In particular, the presented computations suggest the paraboloidal shape of discharge region for device work with the internal cathode. It has been found that for the considered IPD discharge parameters plasma dynamics differs from commonly accepted pattern of concave current-sheet for negative polarization of electrodes (rod cathode and external tube anode). При імпульсному плазмовому напилюванні (ІПН) плазма генерується з робочого газу унаслідок високовольтного потужнострумового розряду в міжелектродній області коаксіального прискорювача. Зростаючі потреби зрозуміння процесів, що відбуваються у плазмовому потоці, стимулювали проведення чисельного моделювання. Дана робота присвячена комп'ютерним дослідженням ІПН прискорювача з внутрішнім електродом-катодом. Детальна структура розрядної області описана в наближенні двовимірної двурідинної магнітогідродинаміки. Зокрема, представлені розрахунки рекомендують параболічну геометрію розрядної області при роботі з внутрішнім електродом-катодом. Показано, що для розглянутих ІПН розрядів При импульсном плазменном напылении (ИПН) плазма генерируется из рабочего газа вследствие высоковольтного сильноточного разряда в межэлектродной области коаксиального ускорителя. Возрастающие потребности понимания происходящих процессов в плазменном потоке стимулировали проведение численного моделирования. Данная работа посвящена компьютерным исследованиям ИПН ускорителя с внутренним электродом–катодом. Детальная структура разрядной области описана в приближении двумерной двужидкостной магнитогидродинамики. В частности, представленные расчеты рекомендуют параболическую геометрию разрядной области при работе с внутренним электродом–катодом. Показано, что для рассматриваемых ИПН разрядов динамика плазмы отличается от общепринятой формы вогнутого токового слоя при отрицательной полярности электродов (стержневой катод и внешняя труба- анод).